Chemotherapy-induced gut microbiota dysbiosis exacerbates cancer-related fatigue in breast cancer patients via neuroimmune-endocrine indicators - Lai, Fengxia; Yuan, Yang; Dong, Haiyan; Guo, Daoxia; Yang, Zhongfang; Tian, Li (Frontiers in Oncology, 2026)
BackgroundBreast cancer patients frequently experience debilitating cancer-related fatigue (CRF) during chemotherapy. Emerging evidence implicates the gut microbiota (GM) and the gut-brain axis in CRF pathogenesis, yet whether pre-chemotherapy GM profiles can predict CRF remains unclear.MethodsThis prospective cohort study enrolled 100 breast cancer patients initiating chemotherapy. GM profiling and fatigue assessment (Visual Analogue Fatigue Scale, Cancer Fatigue Scale) were performed at baseline and the third chemotherapy cycle. Serum levels of neuroimmune-endocrine markers were also measured. Multivariate logistic regression was used to build a predictive model for moderate-to-severe CRF.ResultsPatients experiencing moderate-to-severe CRF at the third chemotherapy cycle demonstrated higher baseline Bacteroidetes/Firmicutes ratios, increased Proteobacteria/Enterobacteriales levels, and reduced abundance of short-chain fatty acid-producing bacteria. The predictive model incorporating baseline GM signatures and clinical covariates achieved an AUC of 0.82, demonstrating good predictive accuracy for moderate-to-severe CRF. Decreased levels of Firmicutes/Blautia in the gut mucosal microenvironment, along with reduced serum brain-derived neurotrophic factor (BDNF), were associated with increased CRF.ConclusionBaseline GM characteristics predict the risk and severity of chemotherapy-induced CRF, potentially through modulation of neuroimmune-endocrine pathways via gut-brain axis. These findings underscore the potential role of GM as a predictive biomarker and a therapeutic target for chemotherapy-induced CRF.